Evaluation of the ESR In Monitoring Treatment of Tuberculosis Patients at The Puskesmas Tuminting, Manado - Jonas Edrian Sumampouw; Yourisna Pasambo; Muh. Ali Makaminan (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Because it may detect inflammation in any condition, the Erythrocyte Sedimentation Rate test is still the most popular laboratory technique for assessing how clinical therapy for infectious infections is working. The goal of the study was to demonstrate that there is a correlation between the administration of anti-TB medications against ESR in TB patients and the progression of treatment for patients with tuberculosis (TB) through ESR. Laboratory testing was part of the descriptive study design. Thirty adult TB patients who met the inclusion criteria had venous blood samples tested for ESR. There were 17 patients in the continuous phase and 13 patients in the starting phase. According to the study, the mean ESR fell from 21,5 mm/hour in the beginning phase to 11,5 mm/hour in the continuation phase.  A correlation test was utilized in the statistical analysis. The correlation r-value was -0,457 and the p-value was 0,006, indicating that the decrease in ESR in patients from the first phase to the continuation phase was not statistically significant. Compared to the beginning phase, TB patients' average ESR readings were lower in the continuous phase. In TB patients, there was a moderate correlation between taking anti-TB drugs and ESR. Abstrak: Uji Laju Sedimentasi Eritrosit masih merupakan metode laboratorium yang paling sering digunakan dalam memantau respon terapi klinis pada penyakit infeksi karena dapat mencerminkan inflamasi pada kondisi apapun. Tujuan penelitian adalah untuk menilai kemajuan pengobatan pada pasien Tuberkulosis) melalui LED dan membuktikan bahwa ada hubungan antara pemberian obat anti TB terhadap LED pada pasien TB. Desain penelitian adalah deskriptif dengan uji laboratorium. Sampel darah vena dari tiga puluh pasien TB dewasa yang memenuhi kriteria inklusi diperiksa ESR. Ada 13 pasien fase awal dan 17 pasien fase lanjutan yang terlibat. Hasil penelitian didapatkan rata-rata ESR pada fase awal dari 21,5 mm/jam menurun menjadi 11,5 mm/jam pada fase lanjutan. Analisis statistik yang digunakan menggunakan uji korelasi. Nilai r korelasi sebesar -0,457 dengan nilai p-value 0,006 menunjukkan bahwa terdapat pengaruh yang kecil dari pemberian obat antituberkulosis terhadap penurunan LED pada pasien dari fase awal hingga fase lanjutan. Rata-rata nilai ESR pasien TB fase lanjutan lebih rendah dibandingkan fase awal. Hubungan antara pemberian obat anti TB terhadap LED pada pasien TB tidak cukup kuat.